2016
DOI: 10.1128/jvi.01243-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Host Species on Topography of the Fitness Landscape for a Plant RNA Virus

Abstract: Adaptive fitness landscapes are a fundamental concept in evolutionary biology that relate the genotypes of individuals to their fitness. In the end, the evolutionary fate of evolving populations depends on the topography of the landscape, that is, the numbers of accessible mutational pathways and possible fitness peaks (i.e., adaptive solutions). For a long time, fitness landscapes were only theoretical constructions due to a lack of precise information on the mapping between genotypes and phenotypes. In recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
1
19
0
6
Order By: Relevance
“…Although specific mutation interactions changed across environments, in most environments there was a general pattern of diminishing returns epistasis. Several other studies have also found pervasive environment dependent epistasis (Caudle et al 2014;Cervera et al 2016;Remold and Lenski 2004;Flynn et al 2013;Li and Zhang 2018). Our results extend this work by describing characteristics of complete fitness landscapes across selective and alternative environments, and examining both global and local mutation interaction effects.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although specific mutation interactions changed across environments, in most environments there was a general pattern of diminishing returns epistasis. Several other studies have also found pervasive environment dependent epistasis (Caudle et al 2014;Cervera et al 2016;Remold and Lenski 2004;Flynn et al 2013;Li and Zhang 2018). Our results extend this work by describing characteristics of complete fitness landscapes across selective and alternative environments, and examining both global and local mutation interaction effects.…”
Section: Discussionmentioning
confidence: 86%
“…One consequence is that fitness trade-offs can be inconsistent, even when considering the effects of a single mutation (Remold 2012). A study of fitness of Tobacco etch potyvirus strains measured across two hosts found that genotypes engineered to contain mutations selected during evolution on one host could either increase or decrease fitness on the original host, and these differences were, at least in part, due to environment dependent epistatic interactions (Cervera et al 2016). The same kind of con-text dependence was seen when comparing cross-resistance of Plasmodium falciparum to two antimalarial drugs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this experimental set up, fitness is just the relative ability of a viral strain to produce stable infectious progeny in a given host (cell type, organ, individual, or species) when the available resources have to be shared with a competitor 5 .Regardless its limitations, at least, this approach provides a metric for ranking viral strains according to their performance in a particular environment/host. Such a fitness measure has been pivotal for quantitatively understanding many virus evolution processes: the effect of genetic bottlenecks and accumulation of deleterious mutations in RNA virus populations 6-8 , the rates and dynamics of adaptive evolution into novel hosts 9, , the pleiotropic cost of host range expansion 10-12 , the cost of genome complexity 13,14 , the cost of antiviral escape mutations 15-17 , the topography of adaptive fitness landscapes [18][19][20] , and the role of robustness in virus evolution 21-23 .But differences in viral fitness should also matter in genome wide studies seeking to understand the mode of action of the viruses (i.e., the precise way they interact with their hosts).Even though it has been argued that an integrative systems biology approach to viral pathogenesis would result in a better understanding of pathogenesis and in the identification of common targets for different viruses, therefore serving as a guide to a more rational design of therapeutic drugs 24-30 , pioneering studies have ignored the high genetic variability of viruses and subsequent differences in fitness and in mode of action. Experimental evidences support that even single nucleotide substitutions have significant effects on viral fitness, regardless they are synonymous or nonsynonymous, or they affect coding or non-coding genomic regions [31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%
“…Regardless its limitations, at least, this approach provides a metric for ranking viral strains according to their performance in a particular environment/host. Such a fitness measure has been pivotal for quantitatively understanding many virus evolution processes: the effect of genetic bottlenecks and accumulation of deleterious mutations in RNA virus populations 6-8 , the rates and dynamics of adaptive evolution into novel hosts 9, , the pleiotropic cost of host range expansion 10-12 , the cost of genome complexity 13,14 , the cost of antiviral escape mutations 15-17 , the topography of adaptive fitness landscapes [18][19][20] , and the role of robustness in virus evolution 21-23 .…”
mentioning
confidence: 99%